An investigation into the non-adoption of soil-cement bricks by the community of the Kei District - Williams, Nomsa (My University, 2002)
Refer to document
Thesis (M. Dev.) -- University of Limpopo, 2002
Keywords: Soil-cement bricks; Rural development; Rural development -- South Africa; Building materials research -- South Africa; Brick houses -- South Africa